2011
DOI: 10.1126/scisignal.2002038
|View full text |Cite
|
Sign up to set email alerts
|

i2 Signaling Promotes Skeletal Muscle Hypertrophy, Myoblast Differentiation, and Muscle Regeneration

Abstract: Skeletal muscle atrophy results in loss of strength and an increased risk of mortality. We found that lysophosphatidic acid, which activates a G protein (heterotrimeric guanine nucleotide-binding protein)-coupled receptor, stimulated skeletal muscle hypertrophy through activation of Gα(i2). Expression of a constitutively active mutant of Gα(i2) stimulated myotube growth and differentiation, effects that required the transcription factor NFAT (nuclear factor of activated T cells) and protein kinase C. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 70 publications
5
86
3
1
Order By: Relevance
“…These cells get committed to myogenic differentiation and fuse with existing muscle fibers. [56][57][58][59][60][61] In vivo skeletal muscle growth is identified by hypertrophy (increase in fiber size) and hyperplasia (increase in fiber number), [62][63][64] while in vitro myogenic differentiation can be quantified by fusion index (ratio of fused nucleus) and area (hypertrophy) of myotubes. 42,43 In addition, maintenance of myotubes is influenced by signals of skeletal muscle protein Figure 1 sF-induced differentiation in hskMcs.…”
Section: Discussionmentioning
confidence: 99%
“…These cells get committed to myogenic differentiation and fuse with existing muscle fibers. [56][57][58][59][60][61] In vivo skeletal muscle growth is identified by hypertrophy (increase in fiber size) and hyperplasia (increase in fiber number), [62][63][64] while in vitro myogenic differentiation can be quantified by fusion index (ratio of fused nucleus) and area (hypertrophy) of myotubes. 42,43 In addition, maintenance of myotubes is influenced by signals of skeletal muscle protein Figure 1 sF-induced differentiation in hskMcs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous G␣ s -coupled GPCRs of the odorant family are transcriptionally regulated during myogenesis and after skeletal muscle injury (80). Intramuscular cAMP can also be stimulated by chronic stimulation of the motor nerve by an implanted nerve cuff in rabbits and rats (131,244 (163). Although many signaling pathways may indirectly modulate intramuscular cAMP signaling via similar pathways or indirect modulation of AC activity, we will limit our discussion to ligands that directly regulate cAMP production.…”
Section: (See Hypertrophy and Injury And Regeneration)mentioning
confidence: 99%
“…Developing mouse muscle expresses G␣ s and two G␣ i isoforms (G␣ i2 and G␣ i3 ); all are downregulated after birth but strongly upregulated in denervated gastrocnemius muscle (220). In skeletal muscle, pertussis toxin-sensitive G proteins containing G␣ i signal via PKC-dependent pathways (135,163) as well as through released G␤␥ in differentiating skeletal muscle cells (61). A very exciting recent study showed that expression of G␣ i2 is sufficient to promote myofiber hypertrophy, oxidative fiber-type switching, myogenic differentiation, and muscle regeneration in mice (163).…”
Section: (See Hypertrophy and Injury And Regeneration)mentioning
confidence: 99%
See 1 more Smart Citation
“…The mitogenic effect of LPA in myoblasts was further confirmed in a subsequent study, in which the LPA action was found to be exerted via ligation of LPA 1 /LPA 3 receptors and activation of the phosphatidylinositol-4,5-bisphosphate 3-kinase pathway [18]. Additionally, a recent study has shown that LPA, acting via Ga i2 , robustly stimulated hypertrophy of myotubes in a protein kinase C dependent manner [19].…”
Section: Introductionmentioning
confidence: 71%